Impaired interoception in Colombian victims of armed conflict with PTSD: a preliminary HEP study - Herrera, Eduar; Gutierrez-Sterling, Daniela; Barrera-Ocampo, Alvaro; Jaramillo, Juliana Orozco; Santamaría-García, Hernando; Birba, Agustina (Frontiers in Psychology, 2025)
Individuals who have been exposed to violence are at high risk of developing mental health problems, particularly posttraumatic stress disorder (PTSD). A prominent example is the experience of Colombia, which has suffered systemic violence for more than half a century. Subjects with trauma-related disorders have problems regulating their emotions and facial emotion recognition (FER), a phenomenon that can be explained from a biological perspective by interoception. We conducted an experimental study using the heartbeat-evoked cortical potential amplitude (HEP) to determine the differences in FER and interoceptive priming in victims of armed conflict in Colombia with PTSD, complex posttraumatic stress disorder (CPTSD), and a control group. The results of behavioral studies indicate that individuals with PTSD and CPTSD exhibit impairments in interoceptive accuracy and deficits in the FER task. Compared with those in both the control and PTSD groups, the group of CPTSD victims demonstrated a decline in FER performance following interoceptive priming relative to exteroceptive priming. At the brain level, compared with controls, individuals with CPTSD presented a reduced amplitude of the HEP in the frontocentral regions during interoceptive processing. Significant differences were observed between the CPTSD and PTSD groups in the right frontal–lateral region during interoceptive priming. Our findings suggest alterations in FER interoception and HEP attenuation in armed conflict victims with PTSD and CPTSD. These results highlight the importance of interoception tasks in understanding the neurobiological mechanisms underlying emotional regulation and recognition in populations exposed to war trauma, and they may offer potential therapeutic strategies and targets for PTSD.